An undergraduate exploratory research on marketability of dog day care and lodging facilities in Quezon City, Metro Manila, Philippines - Cruz, Edeline Mariel J., author; Obafiel, Canee Louise C.
The Philippines is currently tagged as the Dog Capital of East Asia with ratio of dogs to humans surpassing its neighboring countries. Being caring dog-lovers, Filipinos practice responsible dog ownership by being able to provide their dogs all their necessities including socialization with other dogs and humans. In the turn of the century, more and more Filipinos became busy with their jobs and travels compromising the time and attention that their dogs should recieved. As such, dog daycare and lodging facilities emerged, wherein dogs can have a safe place to stay, solving one of the main problems of dog owners - leaving their dogs home alone. This study shows the marketability of dog daycare and lodging facilities in Quezon City, Philippines through the perception of dog owners who experienced and avaiked its services. This study wishes to identify the profile of its market and analyze their assessment of its services in the hopes of contributing to the market and product development of this industry.